2020
DOI: 10.1371/journal.pgen.1008864
|View full text |Cite
|
Sign up to set email alerts
|

­­­­­­Widespread conservation and lineage-specific diversification of genome-wide DNA methylation patterns across arthropods

Abstract: Cytosine methylation is an ancient epigenetic modification yet its function and extent within genomes is highly variable across eukaryotes. In mammals, methylation controls transposable elements and regulates the promoters of genes. In insects, DNA methylation is generally restricted to a small subset of transcribed genes, with both intergenic regions and transposable elements (TEs) depleted of methylation. The evolutionary origin and the function of these methylation patterns are poorly understood. Here we ch… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
88
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(101 citation statements)
references
References 76 publications
(157 reference statements)
13
88
0
Order By: Relevance
“…These enriched functions are in agreement with previous observations that DNA methylated genes in arthropods tend to perform housekeeping functions 6,63 . These predicted functions differ from those of the non-CpG depleted genes (putatively hypomethylated genes), which appear to be involved in signaling pathways, metabolism, and catabolism.…”
Section: Dna Methylationsupporting
confidence: 92%
“…These enriched functions are in agreement with previous observations that DNA methylated genes in arthropods tend to perform housekeeping functions 6,63 . These predicted functions differ from those of the non-CpG depleted genes (putatively hypomethylated genes), which appear to be involved in signaling pathways, metabolism, and catabolism.…”
Section: Dna Methylationsupporting
confidence: 92%
“…Moreover, DNA methylation levels in arthropods, particularly insects, are generally lower than in vertebrates ( Bewick et al., 2017 ). Indeed, given the possibilities of comparing different orders that have distinct DNA methylation patterns ( Bewick et al., 2017 ; Lewis et al., 2020 ), insects have become the model of choice for studying the functional significance of this DNA modification ( Hunt et al., 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…The methylated state alters gene expression by recruiting repressors or by inhibiting the binding of transcription factors. However, dipterans belonging to the "Dnmt2 only" organisms do not contain any of the canonical DNA methyltransferases (Dnmt1 and Dnmt3) (Krauss and Reuter, 2011;Bewick et al, 2017;Provataris et al, 2018;Lewis et al, 2020). The remaining Dnmt2 does not appear to methylate DNA, but instead it methylates tRNA (Goll et al, 2006;Bewick et al, 2017).…”
Section: Additional Layers Of Epigenetic Regulationmentioning
confidence: 99%
“…The low levels of DNA methylation in dipterans are consistent with the proposed residual role of Dnmt2 as RNA methyltransferase. However, the functional significance of Dnmt2-mediated methylation is being challenged in recent years (Takayama et al, 2014;Lewis et al, 2020). For example, this mechanism has been suggested to be involved in immune responses in D. melanogaster (Durdevic and Schaefer, 2013;Bhattacharya et al, 2020), and in this species the encoding gene has been shown to display positive selection signatures (Bhattacharya et al, 2020).…”
Section: Additional Layers Of Epigenetic Regulationmentioning
confidence: 99%